RETRACTED: Alminderej et al. Antimicrobial and Wound Healing Potential of a New Chemotype from Piper cubeba L. Essential Oil and In Silico Study on S. aureus tyrosyl-tRNA Synthetase Protein. Plants 2021, 10, 205 - Fahad Alminderej; Sana Bakari; Tariq I. Almundarij; Mejdi Snoussi; Kaïss Aouadi; Adel Kadri (Plants, 2024)
The journal retracts the article, ‘Antimicrobial and Wound Healing Potential of a New Chemotype from Piper cubeba L. Essential Oil and In Silico Study on S. aureus tyrosyl-tRNA Synthetase Protein’ [...]